Frontispiece: Aromatic Micelles as a New Class of Aqueous Molecular Flasks. Issue 66 (27th November 2017) - Kondo, Kei; Klosterman, Jeremy K.; Yoshizawa, Michito
Abstract : Micelles are one of the oldest classes of supramolecules and typically composed of amphiphilic molecules with aliphatic subunits. This article focuses on the recent development of micellar nanostructures formed from amphiphile compounds with polyaromatic or oligoarylene frameworks. The new aromatic micelles providing polyaromatic shells display superior binding capabilities toward medium to large molecules (for example, Nile red, pentacene, fullerenes, metallo‐phthalocyanines, and carbon nanotubes) in water. For more details, see the Minireview by M. Yoshizawa et al. onpage 16710 ff.